Grants Scheme : 2007 Project Summaries. (Carrick Institute for Learning and Teaching in Higher Education, 2007)
The Grants Scheme enables the Carrick Institute for Learning and Teaching in Higher Education to realise its designated responsibility to provide grants for academics and professional staff to investigate, develop and implement innovations in learning and teaching, and to develop leadership capabilities. This report provides summaries of the projects funded by the scheme in 2007.